A Novel SACS Variant Identified in a Chinese Patient: Case Report and Review of the Literature - Chen, Yuchao; Lu, Xiaodong; Jin, Yi; Li, Dan; Ye, Xiaojun; Tao, Chenjuan; Zhou, Menglu; Jiang, Haibo; Yu, Hao (Frontiers in Neurology, 2022)
Mutations in the SACS gene have been linked to autosomal recessive spastic ataxia of Charlevoix Saguenay (ARSACS). It is a clinically and genetically heterogeneous disease characterized by slow progressive ataxia, spasticity, sensorimotor neuropathy, and a combination of other manifestations, such as lack of spasticity, hearing loss, and epileptic seizures. Currently, there have been very few case reports regarding the SACS gene mutation in Chinese patients. Here, we describe a 35-year-old Chinese patient carrying a novel variant in SACS (c.11486C>T) presenting with progressive ataxia and demyelinating peripheral neuropathy. We then reviewed 22 Chinese cases carrying SACS gene mutations, including our patient. All of them had a cerebellar ataxia gait and showed cerebellar atrophy on brain magnetic resonance imaging (MRI). A total of 28 SACS mutations were identified in these patients. Our study further expands the mutation spectrum of the SACS gene and contributes to the evaluation of genotype-phenotype correlations.